Characterizing forest reduction in Ketapang district, West Kalimantan, Indonesia - ASEP SUNJAYA ADHIKERANA; JITO SUGARDJITO (Society for Indonesian Biodiversity, 2010)
Adhikerana AS, Sugardjito J (2010) Characterizing forest reduction in Ketapang district, West Kalimantan, Indonesia. Biodiversitas 11: 46-54. We have characterized deforestation in the Ketapang district forests when we implemented the Orangutan (Pongo pygmaeus wurmbii) Conservation in Trans-boundary Landscape between Central and West Kalimantan provinces. For the purpose of evaluating the changes in land use and land cover in the study areas, a series of Landsat imageries have been analyzed. Each of the Landsat imagery data set for all study areas was initially classified using unsupervised classification into 13 different land-cover types. Ground truth checks were undertaken for Ketapang district forests and Sungai Puteri peat swamp forest, from which the results were used for the supervised land use classification of these two study areas. Between 1992 and 2000 there was only small conversion of primary forest into secondary forests. During this period barren land remained extensive about 30.17% of the total area of Ketapang district. Both agriculture and plantation areas substantially increased 56% and 55% respectively during 2003, while at the same time the extent ofboth primary and peat swamp forests were considerably reduced up to 15% and 28% respectively. The most striking conversion was from secondary forest to agricultural land and from peat swamp forest to swamp areas. A fraction of lowland forest was also converted into oil-palm plantation which was extended with considerable size into agricultural land. The patterns of land use changes detected in this study indicated a number of possible causes that trigger deforestation in this district include, the local government policy and market demand.Key words: deforestation, habitat fragmentation, Landsat, imagery, land use.